Moderating Effects of MNCs’ Country of Origin in the Relationship between Technology Recipient Characteristics and Degree of Inter-Firm Technology Transfer - Abdul Wahad, Sazali; Che Rose, Raduan; Uli, Jegak; Abdullah, Haslinda (European Journals, Inc., 2009)
While realizing that technologies, knowledge, and competencies are the technology supplier’s main source of competitive advantage, the current inter-firm technology transfer (TT) issue in international joint ventures (IJVs) revolves around the extent of degree of technologies that are transferred by the suppliers to recipient partners in terms of tacit and explicit knowledge. Previous studies on intra-firm knowledge transfer have acknowledged the significant influence of technology actors and facilitators/barriers such as the knowledge transferred, source, recipient and contextual/relational characteristics in the knowledge transfer process. Although previous studies have established the significant relationships between technology transfer determinants and technology transfer, however, these relationships could possibly have been influenced by the MNCs’ country of origin (MNCCOO). Based on the underlying knowledge-based view (KBV) and organizational learning (OL) perspectives, the main objective of this paper is to empirically examine the moderating effects of the MNCs’ country of origin in the relationships between technology recipient characteristics: absorptive capacity (ACAP) and recipient collaborativeness (RCOL) and two distinct dimensions of degrees of technology transfer: degrees of tacit and explicit knowledge within IJVs. Using the moderated multiple regression (MMR), the theoretical models and hypotheses in this study were tested based on empirical data